Arts in Education: A Systematic Review of Competency Outcomes in Quasi-Experimental and Experimental Studies - Schneider, Verena; Rohmann, Anette (Frontiers in Psychology, 2021)
Arts education in schools frequently experiences the pressure of being validated by demonstrating quantitative impact on academic outcomes. The quantitative evidence to date has been characterized by the application of largely correlational designs and frequently applies a narrow focus on instrumental outcomes such as academically relevant competencies. The present review aims to summarize quantitative evidence from quasi-experimental and experimental studies with pre-test post-test designs on the effects of school-based arts education on a broader range of competency outcomes, including intra- and interindividual competencies. A systematic literature search was conducted to identify relevant evaluation studies. Twenty-four articles reporting on 26 evaluation studies were eligible for inclusion, and their results were reviewed in terms of art domains and outcome categories. Whilst there is some evidence of beneficial effects on some competencies, for example of music education on arithmetic abilities, speech segmentation and processing speed, the evidence across arts domains and for different outcomes is limited due to small sample sizes, small number of studies, and a large range of effect sizes. The review highlights that sufficiently powered (quasi-)experimental studies with pre-test post-test designs evaluating arts education are sparse and that the “gold standard” of experimental research comes at the expense of a number of other study characteristics such as sample size, intervention and follow-up length. By summarizing the limitations of the current (quasi-)experimental research, the application of experimental designs is critically assessed and a combination with qualitative methods in mixed-method designs and choice of relevant outcomes discussed.